Unravelling the association between polycentric urban development and landscape sustainability in urbanizing island cities. (October 2022) - Pan, Yi; Qiu, Lefeng; Wang, Zhenlin; Zhu, Jinxia; Cheng, Min
Highlights: The island development of functional polycentricity was lagging than that of the morphological dimension. Spatial regression model performs well in fitting the association between polycentric urban variables and island landscape changes. The effects of dual polycentric urban indicators on island landscape changes varied spatially and temporally. Polycentric urban development generally contributed to fragmented and complex island landscape patterns on the periphery areas of subcenters and reclamation. Abstract: Polycentric urban development has become popular worldwide as expected to generate greater agglomeration externality and facilitate socioeconomic achievements. Despite much insightful work on urban polycentricity in coastal agglomerations or megacities, few studies have focused on how polycentric urban development affects landscape sustainability in vulnerable island cities. This paper characterized the urban polycentricity from the perspective of morphological and functional dimensions during 1990–2020 in Yuhuan island city, China, and quantified the association between polycentric urban variables and island landscape changes by spatial regression. The results showed that there was a mismatch in development between the morphological and functional polycentricity, in which the functional dimension was lagging. In response, island landscape patterns became fragmented and scattered. With the application of GWR models, the effects of two polycentric factors on island landscape changes varied spatially and temporally. The stronger relationships between them were identified in regions where more heterogeneous patterns were presented, such as the subcenters and their surroundings and reclamation areas. These trends were mainly attributed to industrial suburbanization and the development of new economic zone and Damaiyu port. Our findings call for a more balanced functional urban polycentricity; and local-specific landscape effects should be scheduled in island planning practice and sustainable development.